(untitled) (Revista Iberoamericana de Bioética, 2019)
Spanish legal framework on death or end-of-life process is determined by the binding rules in each Self-Governing Community. A comparative analysis of the respective rules will allow us to check the internal coherence of the system and its adequacy to the guidelines provided by the Guide on the decision-making process regarding medical-treatment in end-of-life situations, approved in 2014 by the Council of Europe.